Análise e aprimoramento de requisitos para desenvolvimento de software: um estudo de user stories na perspectiva dos desenvolvedores - Souza, Maria Regina Araújo (Brasil, 2024)
Software development often faces challenges related to requirements' clarity, specificity, and completeness. User stories, widely used in agile methodologies, are a fundamental tool for capturing user needs in a concise manner. However, their writing and refinement still present issues that can negatively impact the development process and the delivery of value to the end user. This study proposes a detailed analysis of publicly available user stories on the internet, combined with personal opinion survey involving developers, intending to identify common problems and suggest improvement practices. The analysis was structured based on the criteria of completeness, clarity, and the INVEST principles (Independent, Negotiable, Valuable, Estimable, Small, and Testable). Additionally, a questionnaire was distributed to developers to validate the analysis conclusions and gather suggestions for enhancing user stories. The results of this study highlight the importance of clear acceptance criteria, the inclusion of adequate technical details, and the need to break down broad stories into smaller, more manageable parts. Developer feedback confirmed the effectiveness of the recommended practices, emphasizing the value of collaboration between teams in creating and refining stories. This work culminates in a practical guide for effective user story writing aimed at the continuous improvement of the agile software development process.